Can text messages reach the parts other process measures cannot reach: an evaluation of a behavior change intervention delivered by mobile phone? - Linda Irvine (Public Library of Science (PLoS), 2012)
Background Process evaluation is essential in developing, piloting and evaluating complex interventions. This often involves observation of intervention delivery and interviews with study participants. Mobile telephone interventions involve no face to face contact, making conventional process evaluation difficult. This study assesses the utility of novel techniques for process evaluation involving no face to face contact. Methods Text messages were delivered to 34 disadvantaged men as part of a feasibility study of a brief alcohol intervention. Process evaluation focused on delivery of the text messages and responses received from study participants. The computerized delivery system captured data on receipt of the messages. The text messages, delivered over 28 days, included nine which asked questions. Responses to these questions served as one technique for process evaluation by ascertaining the nature of engagement with the study and with steps on the causal chain to behavior change. Results A total of 646 SMS text messages were sent to participants. Of these, 613 messages (95%) were recorded as delivered to participants' telephones. 88% of participants responded to messages that asked questions. There was little attenuation in responses to the questions across the intervention period. Content analysis of the responses revealed that participants engaged with text messages, thought deeply about their content and provided carefully considered personal responses to the questions. Conclusions Socially disadvantaged men, a hard to reach population, engaged in a meaningful way over a sustained period with an interactive intervention delivered by text message. The novel process measures used in the study are unobtrusive, low cost and collect real-time data on all participants. They assessed the fidelity of delivery of the intervention and monitored retention in the study. They measured levels of engagement and identified participants' reactions to components of the intervention. These methods provide a valuable addition to conventional process evaluation techniques.